Pre-Service Teachers’ Beliefs about Mathematics - Rejeki, Sri; Sugiyanti, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
This study aims to explorepre-service teachers’ beliefs about mathematics. Those beliefs are defined into beliefs about mathematics as nature, beliefs about learning mathematics, and beliefs about teaching mathematics. Furthermore, each of the dimensions is characterized asconnectionist, transmission, or discovery. This is a survey study. All respondents were given a questionnaire involving nine rating statements using Likert Scale without the “neutral” level. The Cronbach Alpha value for the questionnaire is 0.71, which is considered to be good. In addition, to know more about the pre-service teachers’ beliefs,theyare also asked to elaborate the reasons of the rating they chose for each statement provided in the questionnaire. This study involved 65 pre-service mathematics teachers at a Mathematics Education Study Program of a private university in Indonesia. They were in the beginning of their fourth year atthe university. Based on the results and discussion, it can be concluded that the pre-service mathematics teachers involved in this study tend to have discovery orientation on the dimension of mathematics as nature. On the other hand, both dimensions of learning mathematics and teaching mathematics have transmission orientation. In addition, mathematics is seen as an applicable discipline which demands understanding concepts and communicating ideas.